2022
DOI: 10.3390/ijms23105752
|View full text |Cite
|
Sign up to set email alerts
|

N-Terminal Peptide of PGLYRP1/Tag7 Is a Novel Ligand for TREM-1 Receptor

Abstract: An investigation of innate immunity receptors sheds light on the mechanisms of inflammation and associated immune reactions. One of the key immune regulators is the TREM-1 receptor, which is involved in both inflammation and antitumor immune response. In this article, we have obtained a new ligand for the TREM-1 receptor. The peptide, named N3, is a part of the innate immune protein PGLYRP1/Tag7. It is responsible for activating the TREM-1 signaling pathway. Here, we have demonstrated that the N3 peptide acts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Despite considerable progress in the functional characterization of triggering receptor expressed on myeloid cells 1 (TREM1), TREM1 ligands remain incompletely defined. Two studies have implicated peptidoglycan recognition protein 1 as a ligand for TREM1, either as a complex with bacterially derived peptidoglycan 220 or as an N-terminal peptide 221 . Another study has shown that TREM1 binds to the extracellular cold-inducible RNA-binding protein eCIRP, an endogenous molecule that can be released by damaged tissues 222 .…”
Section: Biology Of Trem1mentioning
confidence: 99%
“…Despite considerable progress in the functional characterization of triggering receptor expressed on myeloid cells 1 (TREM1), TREM1 ligands remain incompletely defined. Two studies have implicated peptidoglycan recognition protein 1 as a ligand for TREM1, either as a complex with bacterially derived peptidoglycan 220 or as an N-terminal peptide 221 . Another study has shown that TREM1 binds to the extracellular cold-inducible RNA-binding protein eCIRP, an endogenous molecule that can be released by damaged tissues 222 .…”
Section: Biology Of Trem1mentioning
confidence: 99%
“…Previously, we investigated the effect of IL-2 on the activation of cytotoxic lymphocytes and for the first time showed that CD4+ and CD8+ cytotoxic T lymphocytes are generated under the action of this cytokine, killing HLA-negative tumor cells via FasL-Fas interaction [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pierce™ Chromogenic Endotoxin Quant Kit (Thermo Fisher Scientific, Rockford, Illinois, USA) was used to confirm absence of LPS in recombinant protein. Tag7 was obtained as described [ 31 ], sTREM-1 was obtained according to [ 30 ]. The BSA was from Sigma (Sigma–Aldrich, St. Louis, MI, USA).…”
Section: Methodsmentioning
confidence: 99%